Análise da microestrutura, parâmetros térmicos e de propriedades mecânicas na solidificação de ligas com alto teor de cobre Al-(x)%Cu-7%Si - Gouveia, Guilherme Lisboa de (2019)
Ternary Al-15%Cu-7%Si and Al-22%Cu-7%Si alloys specimens were obtained by transient directional solidification (DS). This technique is able to provide a very large range of cooling rates and microstructures to be correlated to each other. Overall the microstructures of the directionally solidified samples are constituted by an α -Al dendritic matrix surrounded by two eutectic, that is a binary eutectic, consisting of Si and α -Al, and a bimodal eutectic consisting of cellular type binary eutectic colonies (α-Al + Al2Cu) in a ternary eutectic matrix consisting of (α -Al + Al2Cu + Si). Specially in the case of the Al-22%Cu-7%Si alloy, primary Si particles were also observed. A complete analysis of the dendritic length scale was performed so that relationships of primary and secondary dendritic spacing with cooling rate and growth rate could be derived. The mean dendritic spacing of the DS samples varied: from 85 to 337 μm (λ1) / from 5,7 to 17,7 μm (λ2)/ from 5,5 to 1 7,3 μm (λ3) and from 93,6 to 249 μm (λ1) / from 9,8 to 18,1 μm (λ2) / from 6,6 to 15,1 μm (λ3) for the Al-15wt.%Cu-7wt.%Si and Al-22wt.%Cu-7wt.%Si, respectively. Higher tensile and compressive strengths are associated with the DS alloy containing lower copper content. Furthermore, mechanical properties have been determined for various samples related to different dendritic spacing values so that Hall-Petch type equations could be proposed.